Being Tracked: Responsabilization and Traceability in the Community Supervision of Young Delinquents in Montreal - Nicolas, Sallée; Mestiri, Mohammed Aziz; Bourdages, Jade (Swiss Journal of Sociocultural Anthropology, 2020)
Based on data collected in Montreal, this article looks at the tensions underlying the supervision of young delinquents in the community. More specifically, it questions what happens to support practices in the context of a risk management approach that aims to intensify the monitoring of youths previously targeted as being most at risk of recidivism. To this end, it proposes to study the data resulting from the systematic recording, by the monitoring agents (known as “youth delegates”), of written traces of their activity in computer software dedicated to the traceability of the intervention. It then analyzes the double responsabilization strategy that the content of the software displays. This strategy rests, on the one hand, on the youth themselves, who are called upon to act as the main actors responsible for change, and, on the other hand, on the actors of their environment, in particular their parents, who are asked to collaborate with the youth delegates and, as such, are likely to be recruited as back-up workers for the criminal justice system.